Diagnosis by metagenomic next-generation sequencing of a Talaromyces marneffei bloodstream infection in an HIV-negative child: A case report - Yang, Aimei; Hu, Yan; Chen, Peiling; Zheng, Guilang; Hu, Xuejiao; Zhang, Jingwen; Wang, Jing; Wang, Chun; Huang, Zijian; Zhang, Yuxin; Guo, Yuxiong (Frontiers in Pediatrics, 2022)
Background: Talaromyces marneffei (TM) bloodstream infections are life- threatening in immunocompromised individuals. The lack of specific clinical features for these infections and poor sensitivity associated with routine examination procedures make diagnosis challenging. Untimely diagnosis and delayed antifungal treatment threatens the life of such patients. Case description: We report a case of TM bloodstream infection in a HIV-negative child. A diagnosis of TM was established by blood metagenomic next-generation sequencing (mNGS) of the patient’s blood, which was confirmed by microbiological culture of blood. On admission, this previously healthy male patient was 8-months of age, who presented with recurrent fever and a cough of 6-days in duration. His condition did not improve after antibacterial treatment for 5-days, with significant and recurrent fever and worsening spirit. He was referred to the Department of Pediatrics in our tertiary medical institution with a white blood cell count of 21.5*10^9/L, C-reactive protein of 47.98 mg/L, and procalcitonin of 0.28 ng/mL.A bloodstream infection was not excluded and blood was collected for microbial culture. The patient received a 1-day treatment of cefoperazone sulbactam and 6-days of imipenem cilastatin. Symptoms did not improve and fever persisted. Blood was submitted for mNGS analysis and within 14-hours, 14352 TM reads were detected with a relative abundance of 98.09%. Antibiotic treatment was immediately changed to intravenous amphotericin B combined with oral itraconazole. The condition of the child gradually improved. Blood culture showed TM on the 7th day after hospitalization, confirming bloodstream infection. After the 13th day of hospital admission, the patient’s body temperature dropped below 38°C. He was discharged when his body temperature remained normal for 1-week, which was the 30th day of hospitalization. Oral itraconazole was prescribed with follow up at the outpatient clinic. Conclusion: Infants with immunodeficiency and persistent fever, who do not respond to standard antibiotic treatment, should be considered for possible infection with a rare pathogen. TM infections are rare in children and their detection by conventional microbial culture methods are inadequate for an early diagnosis. mNGS is a rapid detection method that permits early diagnosis of rare infectious agents, such as TM, allowing for improved patient outcomes.